1995
DOI: 10.6028/nist.ir.5591
|View full text |Cite
|
Sign up to set email alerts
|

Post-occupancy evaluation of the Forrestal Building

Abstract: A post-occupancy evaluation was performed on the Department of Energy Headquarters Building (the Forrestal Building) in Washington, D.C. The lighting in the building was retrofitted with new, more energy-efficient, components to meet energy target guidelines. Occupant responses to the indoor environmental conditions, particularly the lighting, were studied to determine the impact of the relighting on the building inhabitants. In addition, physical measures of the lighting and other environmental conditions bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The survey instrument was based on the work of Sanders and Collins (1995), who reported on the post-occupancy evaluation of the government-owned and -operated Forrestal Building. The opportunity to voluntarily participate in the study was advertised, by posting flyers in the library facility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey instrument was based on the work of Sanders and Collins (1995), who reported on the post-occupancy evaluation of the government-owned and -operated Forrestal Building. The opportunity to voluntarily participate in the study was advertised, by posting flyers in the library facility.…”
Section: Methodsmentioning
confidence: 99%
“…A forty‐item questionnaire was developed, which sought to evaluate the effect of lighting design on end‐users' perceptions and opinions at the existing on‐campus library and to gather general opinions regarding sustainability from library end‐users. The survey instrument was based on the work of Sanders and Collins (1995), who reported on the post‐occupancy evaluation of the government‐owned and ‐operated Forrestal Building. The opportunity to voluntarily participate in the study was advertised, by posting flyers in the library facility.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have also found that people prefer relatively bright vertical surfaces (Newsham et al, 2004a(Newsham et al, , 2004cOoyen et al, 1987;Sanders and Collins, 1996;Veitch and Newsham, 2000). Expressed as luminance values, preferred values for walls or cubicle panels should be greater than 30 cd/m 2 (Loe et al, 1994;Newsham et al, 2005;Veitch and Newsham, 2000).…”
Section: Meaningful Lightmentioning
confidence: 99%